Agile…and Offshore. - Armour, Phillip G. (Communications of the ACM, 2007)
The article presents an interview with Doug Grimstead, CEO of Aginity LLC, and Dan Kuhn, CTO of Aginity LLC. In the interview, Grimstead and Kuhn discuss outsourcing, the developmental challenges faced by a company that is working across several continents, and the future of software development in the United States.